2012
DOI: 10.1108/10444061211267263
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive‐experiential self theory and conflict‐handling styles

Abstract: Purpose -The purpose of this paper is to examine how the rational and experiential systems according to the cognitive-experiential self theory (CEST) are related to conflict-handling styles. Design/methodology/approach -Using a correlational design, data were collected using an on-line survey system examining CEST information-processing systems and five conflict-handling styles. A total of 426 undergraduate students, with paid jobs, complete the on-line survey.Findings -Results showed that the rational system,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…The results of Studies 1 and 2 are broadly consistent with those of previous studies that have found positive correlations between self-reported preference for rational thinking and transformational leadership (Cerni et al,2008;Curtis et al, 2017), the integrating style of conflict handling (Cerni et al, 2012), and the core tactics of influence (Curtis & Lee, 2013). In addition, the results provide mixed support for the CELM's proposed relationships between imaginative thinking, emotionality, and effective leadership styles and behaviours.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The results of Studies 1 and 2 are broadly consistent with those of previous studies that have found positive correlations between self-reported preference for rational thinking and transformational leadership (Cerni et al,2008;Curtis et al, 2017), the integrating style of conflict handling (Cerni et al, 2012), and the core tactics of influence (Curtis & Lee, 2013). In addition, the results provide mixed support for the CELM's proposed relationships between imaginative thinking, emotionality, and effective leadership styles and behaviours.…”
Section: Discussionsupporting
confidence: 85%
“…The second-level predictions of the CELM are that thinking style will also predict important leadership behaviours of influencing and conflict handling. However, as noted earlier, previous research has only demonstrated these relationships with self-rated thinking styles, influencing tactics, and conflict handling styles, with workers rather than leaders as the targets rated (Cerni et al, 2012;Curtis & Lee, 2013). Thus, Study 2 examined whether perceptions of leaders' thinking styles, as rated by followers, were related to followers' evaluations of leaders' use of influence tactics and conflict management styles.…”
Section: Correlational and Regression Analysesmentioning
confidence: 89%
See 2 more Smart Citations
“…In a number of recent studies, connections have been found between individual differences in information‐processing styles, as conceptualized in CET, and leadership styles, leadership behaviors, and related outcomes (e.g., Atwater & Yammarino, ; Cerni et al, ; Cerni, Curtis, & Colmar, , , , , ; Curtis & Lee, ; Dubinsky, Yammarino, & Jolson, ; Humphreys & Zettel, ). These findings were a source of inspiration to develop the Cognitive‐Experiential Leadership Model.…”
Section: Cognitive‐experiential Theorymentioning
confidence: 99%